Developments & future directions in the management of chronic pain - Haroutounian, Simon (Henry Stewart Talks, 2019)
Prevalence and burden of chronic pain, Different approaches for pain classification, Assessment: pain severity vs. function, Factors contributing to pain chronification and possible targets for interventions, Current approaches for chronic pain management, Analgesics – efficacy vs. safety, Latest developments in pharmacotherapy for neuropathic pain, Future directions for treatment